2022
DOI: 10.1042/bsr20221443
|View full text |Cite
|
Sign up to set email alerts
|

Leptin alleviates endoplasmic reticulum stress induced by cerebral ischemia/reperfusion injury via the PI3K/Akt signaling pathway

Abstract: Background: Cerebral ischemic/reperfusion injury (CIRI) is a key factor for the prognosis of ischemic stroke (IS). Recent studies have shown that endoplasmic reticulum stress (ERS) may be a target against CIRI and that leptin, a peptide hormone, has neuroprotective activity to mitigate CIRI. Methods: An in vitro CIRI model was induced in primary cortical neurons by oxygen-glucose deprivation and reoxygenation (OGD/R) after pretreatment with LY294002 (10 µmol/L) and/or leptin (0.4 mg/L), and cell viability, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“… 24 Its administration in vivo resulted in a decrease in cerebral infarction, morphological damage and neuronal apoptosis, demonstrating that leptin reduces the secondary events of brain injury after ischemia. 25 The fat content and BMI may be other factors that influence RIPostC inefficacy. To the best of our knowledge, the present study was the first to investigate RIPostC-induced neuroprotection in obese animals.…”
Section: Discussionmentioning
confidence: 99%
“… 24 Its administration in vivo resulted in a decrease in cerebral infarction, morphological damage and neuronal apoptosis, demonstrating that leptin reduces the secondary events of brain injury after ischemia. 25 The fat content and BMI may be other factors that influence RIPostC inefficacy. To the best of our knowledge, the present study was the first to investigate RIPostC-induced neuroprotection in obese animals.…”
Section: Discussionmentioning
confidence: 99%
“…The originally described central actions of leptin were mainly related to the regulation of food intake and energy homeostasis at the hypothalamic level [ 91 ]. Subsequently, it was reported that leptin is also involved in neurogenesis and has neuroprotective actions [ 92 ]. Thus, changes in its functionality may be related to alterations in the regulation of body weight, or different neurodegenerative processes.…”
Section: Functionality Of Leptin and Its Involvement In Pathologymentioning
confidence: 99%
“…Nonetheless, in certain instances, reperfusion of cerebral blood flow not only fails to alleviate disease progression but also exacerbates damage to ischemic brain tissues, recognised as cerebral ischemia-reperfusion injury (CIRI) [ [5] , [6] , [7] ]. Neurological deficits in ischemic stroke are due to a series of complex pathological processes, of which CIRI is the core pathological link [ 8 ]. Thus, attenuating CIRI is essential for the management of acute IS.…”
Section: Introductionmentioning
confidence: 99%